Stimulation of anaerobic organic matter decomposition by subsurface organic N addition in tundra soils. (March 2019) - Philben, Michael; Zheng, Jianqiu; Bill, Markus; Heikoop, Jeffrey M.; Perkins, George; Yang, Ziming; Wullschleger, Stan D.; Graham, David E.; Gu, Baohua
Abstract: Increasing nitrogen (N) availability in Arctic soils could stimulate the growth of both plants and microorganisms by relieving the constraints of nutrient limitation. It was hypothesized that organic N addition to anoxic tundra soil would increase CH4 production by stimulating the fermentation of labile substrates, which is considered the rate-limiting step in anaerobic C mineralization. We tested this hypothesis through both field and lab-based experiments. In the field experiment, we injected a solution of 13 C- and 15 N-labeled glutamate 35 cm belowground at a site near Nome on the Seward Peninsula, Alaska, and observed the resulting changes in porewater geochemistry and dissolved greenhouse gas concentrations. The concentration of free glutamate declined rapidly within hours of injection, and the 15 N label was recovered almost exclusively as dissolved organic N within 62 h. These results indicate rapid microbial assimilation of the added N and transformation into novel organic compounds. We observed increasing concentrations of dissolved CH4 and Fe(II), indicating rapid stimulation of methanogenesis and Fe(III) reduction. Low molecular weight organic acids such as acetate and propionate accumulated despite increasing consumption through anaerobic C mineralization. A laboratory soil column flow experiment using active layer soil collected from the same site further supported these findings. Glutamate recovery was low compared to a conservative bromide tracer, but concentrations of NO3 − and NH4 + remained low, consistent with microbial uptake of the added N. Similar to the field experiment, we observed both increasing Fe(II) and organic acid concentrations. Together, these results support our hypothesis of increased fermentation in response to organic N addition and suggest that increasing N availability could accelerate CH4 production in tundra soils. Graphical abstract: Image 1 Highlights: Field and lab experiments measured the effect of N addition on CH4 production. N addition increased fermentation in all experiments. Increasing Fe(II), DIC, and CH4 indicated increasing anaerobic C mineralization. Non-aromatic DOC was selectively degraded following N addition. Increasing N availability could increase tundra CH4 emissions.